2008
DOI: 10.1211/jpp.60.1.0009
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous penetration of felbinac after application of transdermal patches: relationship with pharmacological effects in rats

Abstract: We have evaluated the percutaneous penetration of felbinac following application of topical patches using a microdialysis technique, and have examined correlations with pharmacological effects. A linear microdialysis probe with a 20-mm dialysis fibre was inserted into the skin of anaesthetized rats. Probe perfusion was started at 2.0 microL min(-1) with physiological saline and after a 60-min baseline sampling of dialysate, 0.1 mL croton oil was applied to the skin surface at a concentration of 8%, v/v. A felb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Also felbinac (transdermal therapeutic system) and diclofenac (spray gel), two topical drugs for treatment of muscle inflammation, have been examined using MD. Based on the high drug concentrations found in the skin and subcutaneous tissues, respectively, both administration modalities were shown to be possible alternatives to orally administered nonsteroidal anti-inflammatory drugs for superficial muscle inflammation [91,117] . Ketoprofen penetration kinetics following application as a transdermal therapeutic system (with the target being intra-articular inflammation) has been measured in the skin as well as in the knee joint by MD.…”
Section: Clinical Studies Of Pharmacokinetics In the Skinmentioning
confidence: 99%
“…Also felbinac (transdermal therapeutic system) and diclofenac (spray gel), two topical drugs for treatment of muscle inflammation, have been examined using MD. Based on the high drug concentrations found in the skin and subcutaneous tissues, respectively, both administration modalities were shown to be possible alternatives to orally administered nonsteroidal anti-inflammatory drugs for superficial muscle inflammation [91,117] . Ketoprofen penetration kinetics following application as a transdermal therapeutic system (with the target being intra-articular inflammation) has been measured in the skin as well as in the knee joint by MD.…”
Section: Clinical Studies Of Pharmacokinetics In the Skinmentioning
confidence: 99%
“…As a potent NSAID, felbinac (FEL) has been widely used for treatment of osteoarthritis, rheumatoid arthritis, muscle inflammation, and acute soft tissue injuries in topical preparations [4][5][6][7]. Currently, FEL patches have been available in Japan and Korea, but the product has a large application area of 70 cm 2 , which is far beyond the desired size (that is, a surface area of ≤40 cm 2 ) and decreased patients' compliance [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, there were many articles reported for the tumor necrosis factor(TNF-α), IL-1,IL-6,IL-8, prostaglandin (PG), iso-prostaglandin F(2)-IsoPs, histamine and other inflammatory cytokines [90][91][92][93][94] to carry out the MD sampling, so as could evaluate the local anti-inflammatory drug pharmacodynamics. Shinkai et al [95] using the croton oil to establish the rat skin inflammation model, after the MD probe was implanted in the subcutaneous, then given the felbinac patch, the MD sample drug concentration was measured, wherein the PGE-2 levels were measured, the results showed that croton oil significantly increased the subcutaneous PGE-2 levels, while providing 0.5% or 3.5% felbinac patch after 2~5 h, the PGE-2 levels were significantly decreased. In Shinkai et al [96] another study had proven that the transdermal ketoprofen significantly reduced the PGE-2 skin content and the joint fluid.…”
Section: The Pharmacodynamics and Mechanism Studymentioning
confidence: 99%